Ecohydroclimatological Research Along the Catacocha-Zamora Transect, Loja and Zamora-Chinchipe, Ecuador - Oñate Valdivieso, F. (2017)
This study reports on ecohydroclimatological research along the Catacocha-Zamora transect in the provinces of Loja and Zamora-Chinchipe, Ecuador. Mean annual precipitation varies between 400 mm in Catamayo, along the study transect, to 2 200 mm in Zamora, to the eastern limit. Altitudinal variations are also marked, between 1 230 m in Catamayo, to 2 930 m in Cerro del Consuelo, to 900 m in Zamora. Ecohydrological and hydroclimatological data are examined with the aim of developing relations to underpin the nascent field of ecohydroclimatology. Applications are envisioned in the management of tropical montane ecosystems.